Olfactory receptor neuron responses of a longhorned beetle, Tetropium fuscum (Fabr.) (Coleoptera: Cerambycidae), to pheromone, host, and non-host volatiles. (December 2015) - MacKay, Colin A.; Sweeney, Jon D.; Hillier, N. Kirk
Graphical abstract: Highlights: First cerambycid study to test pheromone, host, and non-host volatiles with SSR. 31% of ORNs responded to fuscumol, half of which (15%) were fuscumol-specific. 16% of ORNs responded to fuscumol as well as at least one other compound. Male and female T. fuscum did not differ in their ORN responses to fuscumol. Racemic linalool elicited the most responses (43%) of the 13 compounds tested. Abstract: Longhorn wood-boring beetles (Coleoptera: Cerambycidae) use olfactory cues to find mates and hosts for oviposition. Tetropium fuscum (Fabr.) is an invasive longhorned wood-boring beetle originating from Europe that has been established in Nova Scotia, Canada, since at least 1990. This study used single sensillum recordings (SSR) to determine the response of olfactory receptor neurons (ORNs) in the antennal sensilla of male and female T. fuscum to different kinds of olfactory cues, namely host volatiles, non-host volatiles, the aggregation pheromone of T. fuscum (fuscumol), and an aggregation pheromone emitted by other species of longhorn beetles (3-hydroxyhexan-2-one). Each compound had been previously shown to elicit antennal activity in T. fuscum using electroantennography or had been shown to elicit behavioral activity in T. fuscum or other cerambycids. There have been very few SSR studies done on cerambycids, and ours is the first to compare response profiles of pheromone components as well as host and non-host volatiles. Based on SSR studies with other insects, we predicted we would find ORNs that responded to the pheromone alone (pheromone-specialists), as well as ORNs that responded only to host or non-host volatiles, i.e., separation of olfactory cue perception at the ORN level. Also, because male T. fuscum emerge earlier than females and are the pheromone-emitting sex, we predicted that the number of pheromone-sensitive ORNs would be greater in females than males. We found 140 ORNs housed within 97 sensilla that responded to at least one of the 13 compounds. Fuscumol-specific ORNs made up 15% (21/140) of all recordings, but contrary to our prediction, an additional 22 ORNs (16%) responded to fuscumol plus at least one other compound; in total, fuscumol elicited a response from 43/140 (31%) of ORNs with fuscumol-specific ORNs accounting for half of these. Thus, our prediction that pheromone reception would be segregated on specialist ORNs was only partially supported. Our prediction that females would have more ORNs that responded to fuscumol than would males was also not supported, as there was no difference. The stressed-host volatile linalool elicited the most responses of any compound tested, 43% of all recordings.